The Learning Process and Technological Change in Wind Power: Evidence from China's CDM Wind Projects. (12th October 2015) - Tang, Tian; Popp, David
Abstract: The Clean Development Mechanism (CDM) is a project‐based carbon trade mechanism that subsidizes the users of climate‐friendly technologies and encourages technology transfer. The CDM has provided financial support for a large share of Chinese wind projects since 2002. Using pooled cross‐sectional data of 486 registered CDM wind projects in China from 2002 to 2009, we examine the determinants of technological change in wind power from a learning perspective. We use a spatial error model to estimate the effects of different channels of learning—learning through R&D in wind turbine manufacturing, learning from a firm's previous wind project experience, spillovers from industry‐wide project experience, and learning through the network interaction between project developer and turbine manufacturer—on technological change, measured as reductions in projected costs or as increased capacity factor across CDM wind projects. While we find that a project developer's previous experience matters, interactions between a wind project developer and its partner foreign turbine manufacturer lead to the largest cost reductions and capacity factor improvement. We also find that spillovers from industry‐wide experience only exist for wind farm installation. The evidence of industry‐wide spillovers and the joint learning within partnerships between project developers and foreign turbine manufacturers supports the subsidies to users of wind technologies, and policy regimes that promote international collaboration and technology transfer.